Conjugate Properties of Magnetospheric Pc5 Waves: Antarctica‐Greenland Comparison. Issue 2 (17th February 2021) - Pilipenko, Vyacheslav A.; Martines‐Bedenko, Valery A.; Coyle, Shane; Fedorov, Evgeny N.; Hartinger, Michael D.; Engebretson, Mark J.; Edwards, Thom R.
Abstract: An electric circuit analogy for magnetosphere‐ionosphere current systems has two extremes for their driver: a current generator and voltage generator. In the case of a magnetospheric current generator the ground magnetic effect must be nearly the same under low‐conductivity or high‐conductivity ionospheres, whereas in the case of a voltage generator the magnetic response must be larger under a high‐conductivity ionosphere. Theoretical consideration of the field‐aligned current generation by a magnetospheric driver within the framework of the magnetosphere "plasma box" model with asymmetric ionospheres showed that excitation of resonant Alfvenic oscillations should correspond rather to a current generator regime. The asymmetry of Pc5 waves (frequencies about several mHz) recorded at conjugate magnetometers in Greenland and Antarctica has been analyzed from the viewpoint of the voltage/current generator dichotomy. We have selected Pc5 events under contrasting ionospheric conditions, during summer and winter. For resonant frequencies, we have plotted the latitudinal profiles of spectral power and compared the amplitudes of spatial maxima in opposite hemispheres. Along the same profile, latitudinal dependences of the ionospheric height‐integrated conductivities have been reconstructed with the use of the OVATION‐prime (OP) and solar illumination models. During both winter and summer events, the amplitudes of the spectral power peak in Greenland and Antarctica have been found to be about the same, though the OP model predicts a contrast between ionospheric conductivities of 5–10 times. Thus, the interhemispheric properties of Pc5 waves correspond to the current generator regime, as predicted by the magnetospheric plasma box model. Key Points: Pc5 waves recorded at conjugate magnetometers in Greenland and Antarctica are analyzed from viewpoint of voltage/current generator dichotomy During winter/summer events spectral Pc5 power is about the same, though the contrast between ionospheric conductances is 5–10 times The conjugacy properties of resonant Pc5 waves in Greenland and Antarctica correspond well to the current generator regime